2012
DOI: 10.5430/wje.v2n4p102
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Assessment of EFL Reading: Revealing Hidden Aspects at Different Proficiency Levels

Abstract: Dynamic assessment as a complementary approach to traditional static assessment emphasizes the learning process and accounts for the amount and nature of examiner investment. The present qualitative study analyzed interactions for 270 reading test items which were recorded and tape scripted. The reading ability of 9 EFL participants at three proficiency levels of high, mid, and low were assessed dynamically during five weeks of this study. The findings revealed five major data type only available through DA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…It has resulted in a significant improvement regarding different aspects of language learning over the traditional assessment or non-dynamic assessment, which only reveals the abilities that have been already developed . The dynamic score and the analysis of the ZPD make it possible to find out about the abilities that have not developed yet, but can be developed in collaboration with a more knowledgeable person (Ajideh, Farrokhi, & Nourdad, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has resulted in a significant improvement regarding different aspects of language learning over the traditional assessment or non-dynamic assessment, which only reveals the abilities that have been already developed . The dynamic score and the analysis of the ZPD make it possible to find out about the abilities that have not developed yet, but can be developed in collaboration with a more knowledgeable person (Ajideh, Farrokhi, & Nourdad, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for reading, the comparison study of Mardani and Tavakoli (2011) showed the positive effects of DA while Ajideh, Farrokhi and Nourdad (2012) found that learners with different levels of language proficiency might obtain different benefits from DA procedure. But the two studies only centered on the results rather than the processes of DA.…”
Section: Reading and Listeningmentioning
confidence: 95%
“…Pishghadam, Barabadi, and Kamrood (2011) found that low achievers would benefit more than high achievers in L2 DA reading comprehension. However different voices came from Ajideh, Farrokhi, and Nourdad (2012), whose study showed that high proficiency learners had higher transcendence ability than the low proficiency readers. The former study adopted an interventionist approach and group mediation while the latter applied interactionist approach and one-on-one mediation.…”
Section: Figure 1 Trend Of Publicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Setting out to overcome the instruction-testing dualistic view as well as the inadequacy of conventional tests in post-modernistic view of teaching, DA emerges as an innovative system of assessment within the constructivist paradigm (Ajideh, Farrokhi, and Nourdad, 2012;Sternberg and Grigorenko, 2002). However, it has attracted a certain number of criticisms.…”
Section: Da and Its Criticismmentioning
confidence: 99%